2021
DOI: 10.3389/fcell.2021.630777
|View full text |Cite
|
Sign up to set email alerts
|

Mrc1-Dependent Chromatin Compaction Represses DNA Double-Stranded Break Repair by Homologous Recombination Upon Replication Stress

Abstract: The coordination of DNA replication and repair is critical for the maintenance of genome stability. It has been shown that the Mrc1-mediated S phase checkpoint inhibits DNA double-stranded break (DSB) repair through homologous recombination (HR). How the replication checkpoint inhibits HR remains only partially understood. Here we show that replication stress induces the suppression of both Sgs1/Dna2- and Exo1-mediated resection pathways in an Mrc1-dependent manner. As a result, the loading of the single-stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…2A ). Indeed, Mrc1 can differentially regulate resection and HDR at DSBs 41 and it was recently demonstrated that this involves changes in chromatin compaction 42 . Further support that the repair of rNMP-derived lesions is coupled to alterations of chromatin was shown in a recent study in human cells 43 .…”
Section: Discussionmentioning
confidence: 99%
“…2A ). Indeed, Mrc1 can differentially regulate resection and HDR at DSBs 41 and it was recently demonstrated that this involves changes in chromatin compaction 42 . Further support that the repair of rNMP-derived lesions is coupled to alterations of chromatin was shown in a recent study in human cells 43 .…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the fact that deletion of the fork protection protein and damage checkpoint mediator MRC1 can rescue the sensitivity of rtt101 Δ cells to genotoxic agents (Buser et al, 2016) as well as to accumulation of rNMPs ( Figure 2A ). Indeed, Mrc1 can differentially regulate resection and HDR at DSBs (Alabert et al, 2009) and it was recently demonstrated that this involves changes in chromatin compaction (Xing et al, 2021). Further support that the repair of rNMP-derived lesions is coupled to alterations of chromatin was shown in a recent study in human cells (Nakamura et al, 2021).…”
Section: Discussionmentioning
confidence: 99%